Considerations when using microplates and Neubauer counting chamber in ecotoxicity tests on microplastics. (September 2021) - Prata, Joana C.; Venâncio, Cátia; da Costa, João P.; Lopes, Isabel; Duarte, Armando C.; Rocha-Santos, Teresa
Abstract: The ubiquity of microplastics raises issues regarding contamination control measures and laboratory practices. The objective was to adapt the use of counting chambers and plastic microplates on the ecotoxicity evaluation of microplastics. Counting chambers, originally used to quantify cells, can also be used to count high concentrations of microplastics (<100 μm) used in laboratory assays. By decontaminating the chamber and mixing the test solution with Nile Red (1:1), fluorescent particles can be easily counted under optical microscopy. Microplate wells, due to their composition, can be contaminated or release microplastics to the test medium, which can interfere with the results of ecotoxicity assays or spectroscopy readings. A cleaning method based on ethanol was developed, which effectively removed particles by 91% without interfering with microalgae yield. Besides providing practical applications that can improve ecotoxicity assays, this work intends to raise awareness on the need to adapt laboratory practices when working with microplastics. Graphical abstract: Unlabelled Image Highlights: Cleaning counting chambers should be finalized with an air jet. Microplastics stained with Nile Red are visible in counting chambers. 24 well microplates may contain over 14, 000 microplastics per well. A complex cleaning procedure for microplates was developed and tested. Microplate cleaning did not impact Raphidocelis subcapitata yield.